Peran edukasi pajak dalam meningkatkan kesadaran dan kepatuhan wajib pajak - Riyandini, Ariyanti Septy (Maliki Interdisciplinary Journal, 2024)
Tax is one of the primary sources of state revenue used to finance development and social welfare programs. A high level of tax compliance plays a crucial role in the smooth functioning of the tax system and sustainable economic development. However, low public understanding and awareness of taxation are key factors contributing to low tax compliance rates. This article discusses the role of tax education in increasing taxpayer awareness and compliance. Effective tax education helps provide a clear understanding of the importance of taxes as contributions to national development, as well as educating taxpayers on their rights and obligations within the tax system. Various methods, such as seminars, training, media campaigns, and the use of digital technology, can be utilized to reach a wider audience, particularly the younger generation who are more familiar with digital platforms. Collaboration between the government, educational institutions, and society is essential to broaden the reach of this education. With increased public understanding of taxation, it is expected that tax compliance will improve, which will ultimately support the achievement of national development goals. In conclusion, structured and sustained tax education has a significant impact on improving taxpayer awareness and compliance, thereby making a positive contribution to the country's economy.